Brain disconnections link structural connectivity with function and behaviour - Michel Thiebaut de Schotten (Nature Portfolio, 2020)
Brain disconnection after stroke leads to functional deficits whose anatomical basis is poorly understood. Here, based on a collection of stroke imaging, a database of neuroimaging meta-analysis, and high fidelity white matter mapping, the authors provide an atlas of human white matter function.